2022
DOI: 10.3390/brainsci12080966
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of ICAS Patients: Targeting Reperfusion Rather than Residual Stenosis

Abstract: Background and Purpose: Previous studies showed that acute reocclusion after endovascular therapy is related to residual stenosis. However, we observed that reperfusion status but not residual stenosis severity is related to acute reocclusion. This study aimed to assess which factor mention above is more likely to be associated with artery reocclusion after endovascular treatment. Methods: This study included 86 acute ischemic stroke patients who had middle cerebral artery (MCA) atherosclerotic occlusions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The authors showed that reperfusion status was significantly associated with intraprocedural reocclusion, and individuals experiencing effective thrombectomy reperfusion had a smaller proportion of intraprocedural occlusion regardless of residual stenosis severity. Moreover, once effective reperfusion was attained, the delayed reocclusion rate was relatively decreased and did not significantly differ between individuals with severe residual stenosis and patients with mild to moderate residual stenosis [ 12 ].…”
mentioning
confidence: 99%
“…The authors showed that reperfusion status was significantly associated with intraprocedural reocclusion, and individuals experiencing effective thrombectomy reperfusion had a smaller proportion of intraprocedural occlusion regardless of residual stenosis severity. Moreover, once effective reperfusion was attained, the delayed reocclusion rate was relatively decreased and did not significantly differ between individuals with severe residual stenosis and patients with mild to moderate residual stenosis [ 12 ].…”
mentioning
confidence: 99%